POLITIK HUKUM PROGRAM KELUARGA BERENCANA DI INDONESIA - Rahmadhony, Aditya; Puspitasari, Mardiana Dwi; Gayatri, Maria; Setiawan, Iwan (UI Scholars Hub, 2021)
Regime or government change has specificlegal political characteristics, including the Political Law of Family Planning. Each period of government has different views and policies on the implementation of the national family planning program as one of the programs in population control in Indonesia. This study aims to determine the effect of legal politics on the success of the family planningprogram in Indonesia by analyzing statutory regulations in the form of policy rules relating to the family planning program at each government period. The research method used is juridical-normative research through a literature review approach by analyzing policies in the form of laws and regulations and other literatures related to family planning programs. Data collection techniques are through library research and problem approaches through thestatue approaches, historical approaches, and comparative approaches. The results show that there is a relationship between the politics of law or policies issued by a regimeand family planning program intervention.